2018
DOI: 10.3390/inorganics6010025
|View full text |Cite
|
Sign up to set email alerts
|

The Fe Protein: An Unsung Hero of Nitrogenase

Abstract: Although the nitrogen-fixing enzyme nitrogenase critically requires both a reductase component (Fe protein) and a catalytic component, considerably more work has focused on the latter species. Properties of the catalytic component, which contains two highly complex metallocofactors and catalyzes the reduction of N 2 into ammonia, understandably making it the "star" of nitrogenase. However, as its obligate redox partner, the Fe protein is a workhorse with multiple supporting roles in both cofactor maturation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 76 publications
2
39
0
Order By: Relevance
“…Even in Azotobacter vinelandii , a better-studied model strain for nitrogen fixation, difficulties of determining the physiologically relevant reduction potential are prevailing. Measurements in vitro have indicated that the Fe-S cluster of NifH in the “resting” state has a midpoint potential of approximately −310 mV, and that this shifts by at least 100 mV to the negative upon nucleotide binding [61,62]. If the NifH in heterocystous cyanobacteria has a similar reduction potential, it is possible for FdxH to act as a reductant within its physiologically relevant potential [38,39].…”
Section: Balancing the Electron/proton Budgetmentioning
confidence: 99%
“…Even in Azotobacter vinelandii , a better-studied model strain for nitrogen fixation, difficulties of determining the physiologically relevant reduction potential are prevailing. Measurements in vitro have indicated that the Fe-S cluster of NifH in the “resting” state has a midpoint potential of approximately −310 mV, and that this shifts by at least 100 mV to the negative upon nucleotide binding [61,62]. If the NifH in heterocystous cyanobacteria has a similar reduction potential, it is possible for FdxH to act as a reductant within its physiologically relevant potential [38,39].…”
Section: Balancing the Electron/proton Budgetmentioning
confidence: 99%
“…However, substrate reduction was performed by variant MoFe proteins that lacked the FeMo-co and/or contained P cluster precursors (2[4Fe-4S] clusters). In A. vinelandii, the deletion of nifB leads to a MoFe protein that lacks the FeMo-co; instead, the deletion of nifH (Fe protein) leads to a MoFe protein that lacks the FeMo-co and has immature P-clusters (P*, 2[4Fe-4S] pairs) [6]. Remarkably, it was demonstrated that MoFe protein lacking FeMo-co could catalyze the reduction of H + , C 2 H 2 , C 2 H 4 , N 2 H 4 , cyanide (CN − ), carbon monoxide (CO), and CO 2 to products including, H 2 , NH 3 , and alkanes/alkenes spanning C 1 -C 7 [160].…”
Section: Chemical Methods For Electron Transfermentioning
confidence: 99%
“…Electron transfer efficiency to nitrogenase is expected to be improved when using physiological electron donors. While the 1e − reduced [4Fe-4S] 1+ of Fe protein is commonly believed to be the only physiologically relevant state [6], Watt and Reddy discovered that the [4Fe-4S] 1+ cluster can be further reduced by 1e − to a stable all-ferrous [4Fe-4S] 0 state by methyl viologen (MV) [54]. An E o ' of −0.46 V vs. SHE for the 1+/0 couple was reported [54].…”
Section: Electron Transfer From Ferredoxin and Flavodoxinmentioning
confidence: 99%
See 1 more Smart Citation
“…Those genes are responsible for forming nitrogenase complexes that convert unusable atmospheric dinitrogen to useful forms like ammonia and in this process, the nifD and nifK genes encode a dinitrogenase heterotetramer that contains an active site to reduce dinitrogen atoms (Dos Santos et al, 2012). The nifDK genes work together with it redox partner, an iron protein encoded by nifH gene, to complete the structure and function of nitrogenase complex (Jasniewski et al, 2018). Therefore, these genes are important for maintaining mutual associations with a host because defects in the genes may affect the nitrogen-fixing capacity of the symbiont (Spaink, 1998).…”
Section: Introductionmentioning
confidence: 99%